2022
DOI: 10.1017/dce.2022.24
|View full text |Cite
|
Sign up to set email alerts
|

Scalable algorithms for physics-informed neural and graph networks

Abstract: Physics-informed machine learning (PIML) has emerged as a promising new approach for simulating complex physical and biological systems that are governed by complex multiscale processes for which some data are also available. In some instances, the objective is to discover part of the hidden physics from the available data, and PIML has been shown to be particularly effective for such problems for which conventional methods may fail. Unlike commercial machine learning where training of deep neural networks req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…Adding physics into the training of neural operators in addition to any available data enhances their accuracy and generalization capacity for tasks even outside the distribution of the input space. Scalable physics-informed neural networks [59] can be employed to solve high-dimensional problems not possible with traditional finite element solvers, e.g., up to approximately 10 dimensions if not more. Similarly, scalable physics-informed neural operators can also solve high-dimensional problems even in real time and can be used for designing very complex systems.…”
Section: Layout 2: 64 Turbinesmentioning
confidence: 99%
“…Adding physics into the training of neural operators in addition to any available data enhances their accuracy and generalization capacity for tasks even outside the distribution of the input space. Scalable physics-informed neural networks [59] can be employed to solve high-dimensional problems not possible with traditional finite element solvers, e.g., up to approximately 10 dimensions if not more. Similarly, scalable physics-informed neural operators can also solve high-dimensional problems even in real time and can be used for designing very complex systems.…”
Section: Layout 2: 64 Turbinesmentioning
confidence: 99%
“…Therefore, no domain discretisation errors or other solver-based limitations are imposed in PIML calculations. For moving boundaries or domains, PIML does not demand complex computational advancement requirements as traditional computational approaches do [106]. In addition, inherent neural network capabilities can be integrated with physics-based model solutions to overcome most of the limitations of traditional computational approaches [17,107,108].…”
Section: Piml-based Modellingmentioning
confidence: 99%
“…Therefore, PIML can be an alternative approach to the traditional computational approaches where they struggle. For instance, it can extract additional information when scattered data is avail-able and conditions are ill-posed [20,106,112,113]. Cai et al [107] and Blechschmidt and Ernst [108] showed such substantial capabilities in heat transfer and high-dimensional problems, respectively.…”
Section: Piml-based Modellingmentioning
confidence: 99%
“…PINNs were introduced as a new class of data-driven solvers and as a novel approach in scientific machine learning for dealing with problems involving partial differential equations (PDEs) (Cuomo et al, 2022) using automatic differentiation. Several studies have since applied PINNs for a range of scientific problems (Shukla et al, 2022), involving stochastic PDEs, integro-differential equations, fractional PDEs, non-linear differential equations (Uddin et al, 2023), and optimal control of PDEs (Mowlavi and Nabi, 2023). Within engineering, PINNs have been applied to problems in fluid dynamics (Mao et al, 2020; Raissi et al, 2020; Sliwinski and Rigas, 2023), heat transfer (Zobeiry and Humfeld, 2021), tensile membranes (Kabasi et al, 2023), and material behavior modeling (Zheng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%